INOVASI OLAHAN BUAH NANGKA MENJADI CUBADAK BATOKOK MAKANAN KHAS MINANG DI SUNGAI BATANG KABUPATEN AGAM - Naldi, Riko; Hanifah, Dinny; Emely, Bamy (BTJ : Business and Technology Journal, 2024)
Jackfruit is generally used as a vegetable in almost all Indonesian kitchens. Processing also uses a lot of liquids such as water and coconut milk to process it. One of the foods tested in this study was cubadak shell, using liquid oil to process it and using a different method from processed jackfruit in general. This study aims to find out how to make cubadak batokok and to find out the response of the people of Sungai Batang, Agam Regency. The research method used is qualitative with descriptive analysis. The number of informants was 30 people. Data obtained by means of observation, interviews and questionnaires. This research was conducted by making organoleptic test samples with results > 50% of the informants liked Cubadak shells. From the results obtained, it can be interpreted that the people of Nagari Sungai Batang like processed coconut shells and have good opportunities to develop them. Keywords: Innovation, Typical Food, Cubadak Batokok